AEGIS : essays in Mediterranean archaeology : presented to Matti Egon by the scholars of the Greek Archaeological Committee UK - Theodoropoulou-Polychroniadis, Zetta; Evely, R. D. G.; Egon, Matti (Archaeopress Publishing Ltd, 2015)
The honourand of this volume, Matti Egon, has been a great benefactor to museums, schools, universities, and hospitals in the UK and also in Greece. One of these is the Greek Archaeological Committee UK, that she helped found in 1992 - an organization dedicated to informing academe and the public in Britain of archaeological work carried out in Greece, and of enabling the 'brightest minds' of Greece and Cyprus to pursue post-graduate research at British institutions, to the mutual enrichment of both. Some fifty-five graduates have so benefited. This volume offers essays by a good half of those so assisted and is roughly split between the sexes.